Juridical Overview Publishing Photos and Videos of Others Without Permission on Social Media - Putri, Nadiyah Meyliana (Jurnal Scientia Indonesia, 2021)
Every citizen has the right to earn respect for their privacy as well as their dignity as a human being. With the advancement and rapid development of technology, the government adjusted with the establishment of Law Number 28 concerning Copyright and also Law Number 19 of 2016. These adjustments are intended to balance technological advances and protect citizens' rights that have not been regulated in the Law beforehand. This research was normative research that was intended to see and compare the effectiveness of the law in protecting the rights of citizens, as well as to examine the potential or indications that arise from any action. The results of this research were in the form of a review of the effectiveness of the Copyright Law and the Information and Electronic Transaction Law in protecting the rights of citizens in the digital era, as well as what legal consequences will arise for an act.